Debt Collection, Strategic Alliance as Business Strategic Initiatives and Organizational Performance: Empirical Evidence in Kenya (British Journal of Multidisciplinary and Advanced Studies, 2025)
Kenya largely depends on import pharmaceuticals for its healthcare needs with imported medicines accounting for 70% total market valuation in Kenya. Success and profitability of import pharmaceutical companies is therefore important for the sustainability of Kenyan health sector and well-being of its citizens. Import pharmaceutical companies face challenges in organizational performance which include Profit, market share, customer retention and inventory turnover. The objective was to establish the effect of debt collection initiative and strategic alliances initiative on organizational performance of import pharmaceutical companies in Kenya. Balanced Scorecard model was used to anchor organizational performance. Descriptive research design was utilized. The taget population under study was 6356 key employees in 125 registered import pharmaceutical companies. Data was collected using open and closed ended   questionnaire from 376 employees selected using stratified random sampling. The pilot study involved 38 respondents from the target population. Reliability was tested using Cronbach's alpha and the computed coefficient was 0.808. Content validity was determined using content validity index. (CVI) of 0.8. Data was analyzed using descriptive and inferential statistics. Findings indicated that debt collection and strategic alliance initiatives had a meaningful positive correlation with organizational performance of import pharmaceutical companies in Kenya, with strategic alliance initiatives showing the strongest relationship (r = 0.790, p < 0.001). Debt collection initiatives also had a strong correlation (r = 0.748, p < 0.001). Regression analysis showed that strategic alliances and debt collection initiatives had significant effect on organizational performance.  In conclusion debt collection processes should be strengthened through proactive monitoring and digital payment. Organizations should strengthen strategic alliances with suppliers, healthcare institutions, and regulators in order to enhance market expansion and compliance. Research ethics was upheld throughout the study.  Findings are relevant to policy makers, industry stakeholders and in designing procedures and guidelines that aid the success and resilience of the import pharmaceutical sector, ultimately benefiting the health industry in Kenya. The research findings lay a foundation for future studies aimed at identifying and implementing effective business strategic initiatives tailored to the needs of import pharmaceutical companies.